Advance Audit - Practical Audit Tool for Improving Urban Mobility Plans - Dana Sitanyiova; Sona Masarovicova (Communications, 2014)
This paper presents the methodology and the results of the ADVANCE project. ADVANCE supports cities and municipalities on their way towards a more sustainable urban mobility, thus assisting them to set up and improve the quality of Sustainable Urban Mobility Plans (SUMPs) and policies. ADVANCE has developed an audit scheme designed by an interdisciplinary team of mobility experts, to assess the quality of the cities' mobility plans. Thereby, it contributes to the take-up of Sustainable Urban Mobility Plans in Europe.